Where is shakespeare? Locality and performative translation - Alexander C. Y. Huang (Ilha do Desterro)
It has become de rigueur in scholarly inquiries to reconceptualize critical terms and to question commonplace ideas. However, the locality of performative translations of Shakespeare is a logical extension of the worn and hard-pressed question about the nature of Shakespeare’s text and its afterlife. There is indeed only one Mona Lisa, and its location can be precisely pin-pointed. The existence of canonical drama with an infinite range of (performative) signification is a different story.